Analysis of Career Interest Levels Among Twelfth Grade Students at Talang Ubi Senior High School - Ramelia fouryanti; Istiqomah Istiqomah; Lidya Meylisa; Habibullah Habibullah; Alrefi Alrefi; Anasari Anasari (Universitas Sriwijaya, 2026)
This study aims to identify and analyze the career interests of twelfth-grade students at SMAN 2 Unggulan Talang Ubi based on assessment results intended to support career decision-making aligned with students’ abilities and personal characteristics. This research employed a quantitative approach using a descriptive survey design conducted during the even semester of the 2025/2026 Academic Year. A total of 88 twelfth-grade students participated in the study and were selected through a total sampling technique. The instrument used was the Career Interest Instrument developed by the Counseling Trust Center, consisting of a five-point Likert scale designed to measure the six dimensions of the RIASEC model: Realistic, Investigative, Artistic, Social, Enterprising, and Conventional. Data were analyzed descriptively by calculating the total score for each dimension, identifying the dominant interest type, and presenting the findings in percentages. The findings indicate that students’ career interests were predominantly characterized by the Social (72%) and Investigative (67%) types. Meanwhile, the Artistic (48%), Conventional (45%), and Enterprising (40%) types were categorized as moderate to high. In contrast, the Realistic type showed the lowest percentage (19%), although the majority of students in this dimension were classified within the moderate category (53%). These findings suggest that students tend to prefer social interaction and analytical activities over technical or practical tasks. This study provides empirical insights into students’ career interest profiles and offers a foundation for guidance and counseling services to design more targeted and personalized career development programs.